Comportamento do amendoim forrageiro em vegetação campestre e em consorciação com Tifton 85 no litoral Sul, Rio Grande do Sul. - Cassal, Vivian Brusius (2010)
There were two experiments conducted in the field, area of at the Estação Experimental Terras Baixas (ETB) - Embrapa Clima Temperado, Capão do Leão- RS, during the period at , respectively October 2007 to November 2008 and december 2008 to january 2010. The objective of first study was to evaluate the practical application of herbicide, overseeded annual ryegrass and grazing for the introduction of peanut in natural pasture. The experiments were conducted from October 2007 to November 2008, at the Estação Experimental Terras Baixas (ETB) - Embrapa Clima Temperado, Capão do Leão - RS. The treatments were arranged in a randomized block design in split plots with four replications. The plots were represented by the treatments with and without herbicide (commercial herbicide Glyphosate at a dosage of 3L ha-1). The subplots were defined by the absence of peanut, the presence of peanut, the presence of peanut overseeded with annual ryegrass. The sub sub-plots were made by with and without grazing in winter and early spring. The frequencies of species of native pasture were not influenced by grazing and overseeded ryegrass. The introduction of peanut is benefited by the herbicide. However, it is a practice that causes a significant reduction of forage species of forage interest. The overseeded of annual ryegrass as a practice in the introduction of peanuts provides a favorable environment for the difficulties of winter to the legume. The second study was objective was to evaluate the intercropping of forage peanut and Tifton 85 submitted to coutting in Autumn, through structural characteristics and dry matter yield. The experiment was conducted from December 2008 to January 2010, at the Estação Experimental Terras Baixas (ETB) - Embrapa Clima Temperado, Capão do Leão - RS.The area was fertilized with 60 kg ha-1 P2O5, 80 kg ha-1 K2O and 20 kg N ha-1 at December 15 ,2009. Treatments were arranged in randomized complete blocks in split plots with four replications. The plots of 20m2 each, consisted of three row spacings and seedlings of Tifton 85 (1m x 1m, 1m x 0.75m and 1m x 0.50m) and three spacings among of plants Tifton 85 (no forage peanuts, one line and two lines forage peanuts). April 17, 2009 these parcels were divided in half, getting cut autumnal management (with and cut) leaving a 11 residue of 5 cm of soil. From May to September, at intervals of 30 days, evaluations was made of structural characteristics of Tifton 85 and forage peanuts. After cutting autumnal in September 24, November 20,2009 and January 13, 2010 cuts were performed to evaluate the dry matter yield of Tifton 85 and peanuts. Intercropping with peanut and cutting autumnal change the structural characteristics of Tifton 85. The DM yield of Tifton 85 (spring and summer) is less cut-autumn when the temperature does not limit its growth.